Prototype of Fuel Liquid Level Monitoring System at Gas Station Hidden Tank Using the Internet of Things (IoT) - Triuli Novianti; Winarno Winarno (Jurusan Teknik Elektro Universitas Trunojoyo Madura, 2024)
Currently, the availability of fuel oil (BBM) to the community is critical. One way to anticipate delays in supply and empty fuel stocks at refueling stations (petrol stations) is to periodically monitor the fuel liquid level with a Stick Sounding Meter measuring device dipped in the bottom of the tank. Monitoring uses the Internet of Things (IoT) concept, which can integrate surveillance system devices with the Internet network. The system uses an ultrasonic sensor mounted horizontally on the tank's liquid surface to detect the fluid level's distance and an ESP32 NodeMCU to communicate with ThingSpeak, an IoT device. If the tank's liquid exceeds 20% of its capacity, the test results will be displayed in real-time onThingSpeak, and a notification will be sent to the field. Therefore, both petrol station officers in the field and admins can monitor more efficiently. Ultrasonic sensor tests, data transmission accuracy, and fuel liquid levels are some of the stages carried out. Tank 1 has an accuracy rate of 97.066%, and Tank 2 has an accuracy rate of 95.451%.